Giant Barocaloric Effect at the Spin Crossover Transition of a Molecular Crystal. Issue 23 (15th April 2019) - Vallone, Steven P.; Tantillo, Anthony N.; dos Santos, António M.; Molaison, Jamie J.; Kulmaczewski, Rafal; Chapoy, Antonin; Ahmadi, Pezhman; Halcrow, Malcolm A.; Sandeman, Karl G.
Abstract: The first experimental evidence for a giant, conventional barocaloric effect (BCE) associated with a pressure‐driven spin crossover transition near room temperature is provided. Magnetometry, neutron scattering, and calorimetry are used to explore the pressure dependence of the SCO phase transition in polycrystalline samples of protonated and partially deuterated [FeL2 ][BF4 ]2 [L = 2, 6‐di(pyrazol‐1‐yl)pyridine] at applied pressures of up to 120 MPa (1200 bar). The data indicate that, for a pressure change of only 0–300 bar (0–30 MPa), an adiabatic temperature change of 3 K is observed at 262 K or 257 K in the protonated and deuterated materials, respectively. This BCE is equivalent to the magnetocaloric effect (MCE) observed in gadolinium in a magnetic field change of 0–1 Tesla. The work confirms recent predictions that giant, conventional BCEs will be found in a wide range of SCO compounds. Abstract : A giant barocaloric effect is found at low pressures in a near‐room‐temperature spin‐crossover molecular crystal. Structural data obtained by neutron diffraction are correlated with magnetic data and heat‐capacity studies under hydrostatic pressure. This first experimental study of the barocaloric potential of spin‐crossover compounds provides motivation for a wider examination of the material class.